S. Pearce’s model for studying objects and its application to a baptismal cross - Tranta, Alexandra (Journal of Integrated Information Management, 2024)
This paper applies S. Pearce’s model for studying objects to a family heirloom, a baptismal cross. This model is a mnemonic device, not a system of inviolable rules. Furthermore, it is shown that the interpretative process needs to encompass not only information about the object, but also a new perception of the range of philosophical and technical concepts that shape the interpretation of material culture. It is also necessary to stress the understanding and applying the theory of the model for studying objects, realising the degree to which discussing objects contributes to and illuminates different aspects of material culture, given that learning is influenced by personal elements, too, as demonstrated by contemporary museum studies and studies of material culture. Purpose: To contribute to the study of material culture, as well as to explore the possibility of delving deeper into a number of its fields through a single object. Design/methodology/approach: To apply S. Pearce’s model for studying objects to a family heirloom. Findings: The unexpectedly rich interdisciplinary approach that emerged from the study of an object with no “museum” value, as well as its capacity to “narrate” stories. Practical value: Understanding and applying the theory of the model for studying objects, realising the degree to which discussing objects contributes to and illuminates different aspects of material culture, given that learning is influenced by personal elements, too: one’s interests, inclinations, the manner in which one prefers to learn, etc., as demonstrated by Falk & Dierking [1]. Originality/value: Examining how an object, using S. Pearce’s model for studying objects, a foundation stone in the study of material culture, can be perceived through a broader and more interesting feel for its inherent meaning, instead of exclusively through its narrow morphological sense, remains relevant.